Initiation of cassava callus culture and its prospect for starch production: a systematic mapping study - Mohd Sofri, Nur Syazwani Nadhirah; Mohamad Puad, Noor Illi; Nik Ahmad Sabri, Nik Nurul Adnina; Abu Ubaidah, Afiq Syazwan; Hamzah, Fazlena; Abduh, Muhammad Yusuf (UPM Press, 2024)
Mass propagation of cassava on several hectares of arable land due to increasing demand for its starch is not feasible due to land availability, pests and disease invasion, and long cultivation period. Plant cell culture technology is a promising solution despite the scarcity of cassava callus culture for starch production applications. Therefore, a systematic mapping study (SMS) was performed to identify the applications of cassava tissue culture and its prospects in starch production and investigate the important parameters for cassava callus culture initiation. The SMS began with formulating research questions (RQs), conducting searches on various databases, collecting and screening related articles, and extracting and mapping the selected articles. A total of 56 of 589 articles in the initial searching phase were chosen to be used as references to answer each RQ. The extracted data indicates that cassava tissue culture was mostly used for micropropagation, while starch production from its tissue culture is still limited. Basal medium and plant growth regulators influence cassava callus culture initiation most. The findings of the SMS offer a better understanding of cassava tissue culture and the prospects of producing cassava starch.